1986
DOI: 10.1007/bf02902242
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthate allocation and productivity of latex vessels inHevea brasiliensis

Abstract: Manipulations of production systems in rubber tree which were intended to improve sucrose translocation in tapped bark resulted in an increase of latex sucrose and of latex production and reduced the incidence of nonyielding laticiferous tissue. This was achieved by shortening the tapping cut from full to half spiral, by changing the descending direction into an ascending mode of tapping or by annual change-over of tapping panel allowing for a longer time the regeneration of bark removed above the location of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Laticifers are regarded as a strong sink for sucrose and need to be adequately supplied exogenously with sucrose to meet their high carbon and energy demands (Tupy, 1973;Eschbach et al, 1986;Silpi et al, 2007). Based on a few circumstantial observations, active transport across the plasma membrane of laticifers had been hypothesized as the main route of sugar uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Laticifers are regarded as a strong sink for sucrose and need to be adequately supplied exogenously with sucrose to meet their high carbon and energy demands (Tupy, 1973;Eschbach et al, 1986;Silpi et al, 2007). Based on a few circumstantial observations, active transport across the plasma membrane of laticifers had been hypothesized as the main route of sugar uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was observed that most of soluble sugars (TSS) were comprised of reducing sugars, which indicated that sucrose hydrolysis by invertase isoforms were present in that tissue which led increased hexose availability for glycolytic route and consequently enabled greater IPP production. Work with sucrose ( 14 C) application in tapping panel resulted radioactivity appearance in cytosolic fraction of latex that was collected, and process was enhanced by Ethel ® stimulation (Eschbach et al, 1986). In general, latex production in rubber tree bark is related to regeneration of new latex quantities and depends on frequency at which tapping is performed.…”
Section: Water Content Reducing Sugars Total Soluble Sugars and Sucmentioning
confidence: 99%
“…The physiological profile, through sucrose, inorganic phosphorus, thiol group and latex dry rubber content is taken into account as secondary criteria in order to assess the influence of the intensity of rubber biosynthesis metabolism. The physiological profile also helps to determine the ability of clones to bear tapping and hormonal stimulation related stress [16,17,18,19,20]. The clones received by Côte d'Ivoire in international exchanges with rubber tree research institutes are tested directly in LSCT.…”
Section: Introductionmentioning
confidence: 99%